Adult metabolic syndrome in Peru - Pajuelo, Jaime (2007)
Objective: To determine the prevalence of metabolic syndrome in Peruvian adult population. Materials and Methods: We studied 4091 persons over 20 year-old; 50,4% belonged to the female gender and 49,6% to the male gender. These persons were chosen by a triepatic conglomerate sample which represents national level and the following spaces: Metropolitan Lima, remaining coast, urban highland, rural highland, and the selva. Weight, height, waist circumference, arterial blood pressure were determined as well as triglycerides, HDL cholesterol and glucose. For metabolic syndrome diagnosis the ATP III criteria were used. Results: National prevalence of metabolic syndrome was 16,8%. In Metropolitan Lima (20,7%) and the remaining coast (21,5%) the metabolic syndrome was above national prevalence. The lower values were found in rural highland with 11,2%. Female gender (26,4%) broadly exceeded the male gender (7,2%). Metabolic syndrome was more prevalent in obese rather than overweight persons. Metabolic syndrome increased as one got older. As weight circumference increased, the other variables followed the same pattern. Conclusions: In Peru 2 680 000 persons present metabolic syndrome and are in great health risk, because of the different alterations which may occur. As the main reason of this problem is overweight and obesity, it is necessary to implement strategies to fight them. These strategies are widely known: healthy nourishment and physical activity.